Effective behavior change techniques to promote physical activity in adults with overweight or obesity: A systematic review and meta‐analysis. (5th May 2021) - Carraça, Eliana; Encantado, Jorge; Battista, Francesca; Beaulieu, Kristine; Blundell, John; Busetto, Luca; van Baak, Marleen; Dicker, Dror; Ermolao, Andrea; Farpour‐Lambert, Nathalie; Pramono, Adriyan; Woodward, Euan; et al.
Summary: Multicomponent behavior change interventions are typically used in weight management, but results are largely heterogeneous and modest. Determining which techniques (behavior change technique [BCTs]) are more effective in changing behavior is thus required. This study aimed to identify the most effective BCTs for increasing physical activity (PA) in digital and face‐to‐face behavior change interventions in adults with overweight/obesity. Four databases were searched for eligible studies until October 2019. BCTs were coded using BCTTv1 and MBCT taxonomies. Sixty‐two RCTs were included. Meta‐regressions were performed to explore BCTs' moderating role. Five BCTs showed significant moderator effects on PA in digital interventions: goal setting behavior, goal setting outcome, graded tasks, social incentive, and self‐monitoring of behavior (adjusted R 2 's = 0.15–0.51). One BCT showed significant moderator effects on PA in face‐to‐face interventions, behavioral practice and rehearsal (adjusted R 2  = 0.22). Multivariate and sensitivity analysis generally led to similar findings. Effective BCTs for increasing PA in adults with overweight/obesity in digital and face‐to‐face interventions seem to differ. Evidence suggests that using goal setting, social incentive, and graded tasks might help improve PA in digital interventions while avoiding inconsistent self‐monitoring of behavior . In face‐to‐face interventions, prompting behavioral practice and rehearsal might lead to better PA outcomes. Still, further studies are needed. Implications of the current findings are discussed.